2023
DOI: 10.1002/advs.202301178
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Metal Batteries with Long Cycle Life Using a Hydride‐Based Electrolyte and Copper Sulfide Electrode

Abstract: As potential alternatives to Li-ion batteries, rechargeable Ca metal batteries offer advantageous features such as high energy density, cost-effectiveness, and natural elemental abundance. However, challenges, such as Ca metal passivation by electrolytes and a lack of cathode materials with efficient Ca 2+ storage capabilities, impede the development of practical Ca metal batteries. To overcome these limitations, the applicability of a CuS cathode in Ca metal batteries and its electrochemical properties are ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Complex hydrides are found to be suitable candidates for solid-state electrolytes in batteries . Orimo et al reported that borohydrides and derivatives are fast Li + conductors after transferring to the hexagonal high-temperature phase. …”
Section: Introduction To Metal Hydridesmentioning
confidence: 99%
“…Complex hydrides are found to be suitable candidates for solid-state electrolytes in batteries . Orimo et al reported that borohydrides and derivatives are fast Li + conductors after transferring to the hexagonal high-temperature phase. …”
Section: Introduction To Metal Hydridesmentioning
confidence: 99%
“…With the growing global demand for clean energy, the development of renewable energy generation and storage technologies has become a hot topic. In recent years, calcium-ion batteries (CIBs) have garnered widespread interest due to their abundant resources, cost-effectiveness, and low standard electrode potential of Ca (−2.87 V vs SHE) . However, the reversible stripping/plating of Ca metal is not observed in most conventional electrolytes (e.g., Ca­(ClO 4 ) 2 , Ca­(BF 4 ) 2 , or Ca­(TFSI) 2 in a mixed propylene carbonate/ethylene carbonate solvent) at room temperature. , This is mainly due to the formation of a surface passivation layer on a Ca metal anode in these electrolytes, which impedes Ca 2+ transfer through the anode/electrolyte interface .…”
Section: Introductionmentioning
confidence: 99%
“…To meet society’s growing needs for renewable energy storage, novel battery chemistries with higher energy density and lower cost than Li-ion batteries need to be developed. , Ca metal batteries have been proposed as alternatives to Li-ion batteries due to the greater crustal abundance (41,500 mg/kg for Ca vs 20 mg/kg for Li) and anode capacity (1337 mAh/g for Ca metal anodes vs 372 mAh/g for Li/C 6 anodes). Despite these advantages, development of Ca metal batteries has been limited. , …”
Section: Introductionmentioning
confidence: 99%